2008
DOI: 10.1111/j.1468-1331.2008.02158.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of CBFV and time characteristics of oxygen‐induced acute CNS toxicity in humans

Abstract: During exposure to 280 kPa oxygen at rest a constant delay of approximately 20 min precedes the onset of central nervous oxygen toxicity. An increase in CBFV may indicate the impending seizure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Interestingly, in contrast to the cerebral vasoconstriction normally observed during pure O 2 breathing, symptoms are preceded by a paradoxical increase in cerebral blood flow velocity [ 88 ] (Fig. 2 ), which is referred to peroxynitrite (ONOO − ) formation resulting from the reaction of NO with the superoxide radical (O 2 − ) [ 89 ], and thereby causing a dysregulation of the endogenous NO availability [ 46 , 90 ].
Fig.
…”
Section: (Patho)physiology Of Hyperoxia: Pulmonary Vascular Metabolmentioning
confidence: 99%
“…Interestingly, in contrast to the cerebral vasoconstriction normally observed during pure O 2 breathing, symptoms are preceded by a paradoxical increase in cerebral blood flow velocity [ 88 ] (Fig. 2 ), which is referred to peroxynitrite (ONOO − ) formation resulting from the reaction of NO with the superoxide radical (O 2 − ) [ 89 ], and thereby causing a dysregulation of the endogenous NO availability [ 46 , 90 ].
Fig.
…”
Section: (Patho)physiology Of Hyperoxia: Pulmonary Vascular Metabolmentioning
confidence: 99%
“…Simultaneous to this increase in CBF, the cortical electroencephalography (EEG) activity increases (Bean and Coulson, 1971; Visser et al, 1996b). This increase in CBF and cortical EEG activity precedes convulsions (Bean and Coulson, 1971; Visser et al, 1996a,b; Demchenko et al, 2001; Koch et al, 2008). The exact mechanism though which ROS cause convulsions is not entirely clear.…”
Section: Central Nervous System Toxicitymentioning
confidence: 99%
“…Although the exact mechanism is not fully understood, currently, the most plausible explanation is related to an overflow of reactive oxygen species (ROS) in the brain after an increase of cerebral blood flow (CBF) (Visser et al, 1996a; Koch et al, 2008). Due to the increased PO 2 in plasma there is an auto oxidation of nitric oxide ( · NO) to several ROS, of which peroxynitrite (ONOO − ) is the most important (Goldstein and Czapski, 1995; de Groot et al, 2004).…”
Section: Central Nervous System Toxicitymentioning
confidence: 99%
“…Data for hyperoxic exposures at rest in immersion or in dry conditions -exposure time, partial pressure of oxygen (PO 2 ), and appearance or absence of CNS-OT, were extracted from a number of studies compiled by Harabin (1993), and from Koch et al (2008). Evidently there are ample data on hyperoxic exposures at rest which were not reported in a proper way for our analysis (exact condition for each single exposure).…”
Section: Data Derivationmentioning
confidence: 99%
“…However, because these were gathered from naval oriented studies, we believe that the subjects were healthy males. Koch et al (2008) state that their data were from healthy, elite Navy combat divers. As in our previous study (Arieli et al, 2002), we selected the symptoms suggested by Harabin et al (1995) as indicating a positive finding of CNS-OT: nausea, numbness, dizziness, twitching, hearing and visual disturbances, convulsions and unconsciousness.…”
Section: Data Derivationmentioning
confidence: 99%